The Effect Of Participative Leadership, Motivation, Organizational Commitment and Job Satisfaction On Organizational Citizenship Behaviour - Sari, Ina Fitriani; Atmaja, Dodi Ria (Lentera Ilmu Nusantara, 2025)
Organizational citizenship behaviour is a form of employee contribution that can improve teamwork and smooth activities in the workplace, this behavior is often not noticed or not appreciated, so it is important to understand what makes someone willing to do these actions voluntarily. The aims to show the perception of employees regarding the influence of these factors on organizational citizenship. The study analyzed the influence of participative leadership, motivation, organizational commitment and job satisfaction on organizational citizenship behavior, using survey methods and sampling of 120 respondents by purposive sampling of staff and non-managerial employees in the Tangerang City Manufacturing Industry, as well as the analysis method. The study used SEM-PLS with SmartPLS 4. Results show that participative leadership, motivation, organizational commitment, and job satisfaction significantly affect organizational citizenship behavior. The combination of these four factors can provide a significant positive understanding of the increase in organizational citizenship behavior, and helps leaders to support employee initiative and volunteerism in their workplace.